Da eclesiologia de comunhão do Vaticano II ao Movimento Regnum Christi : uma perspectiva eclesiológica dos cristãos leigos - De Carli, Vitoria Bertaso Andreatta (2017)
This dissertation seeks to elucidate the Ecclesiology typical of the International Ecclesiastical Catholic Regnum Christi Movement in relation to the ecclesiological model of the Vatican Council II in order to establish its reception by the Regnum Christi Movement. The structure of the dissertation is divided into three sections. The first one deals with the Ecclesiology of the Vatican Council II, having as a starting point a historical approach and the importance that it had in the life of the Church in the 20th century. The ecclesiological documents of Vatican II are studied as a point of reference, especially the Dogmatic Constitution Lumen Gentium and the Pastoral Constitution Gaudium et Spes to discover the ecclesiology of communion as the key ecclesiological conception of Vatican II. Among the themes of this Ecclesiology, we opted to approach the laity in view of the nature of Regnum Christi. The second section investigates the history, charisma, identity, mission, nature and the finality of Regnum Christi to be able to identify the ecclesiological model adopted by it; it addresses and analyses the reform process which started in 2010, as well as Borrador del Estatuto General del Regnum Christi as the most recent expression of the Ecclesiology of the Movement. The third section prioritizes Vatican II Ecclesiology in the Regnum Christi Movement from the conception of the Church as communion and in the last part, it analyses what concerns the life of the lay member, the dimension of laity in the reality of this ecclesial movement comprised primarily by lay members. It concludes by the recognition of the Regnum Christi Movement as one of the current protagonists of the Ecclesiology of communion, seeking to accomplish the primordial evangelizing mission in communion with all the Church.